2023
DOI: 10.1093/neuonc/noad073.285
|View full text |Cite
|
Sign up to set email alerts
|

Othr-03. Classification of Brain Tumors by Nanopore Sequencing of Cell-Free Dna From Cerebrospinal Fluid

Abstract: For exact molecular diagnosis of CNS tumors, tumor tissue obtained through surgery is usually needed. However, knowledge on the molecular tumor type beforehand might influence surgical strategies and reduce surgery-associated risks. Molecular analyses of liquid biopsies have therefore gained increasing interest in order to secure diagnosis before surgery or to replace surgery in rare instances. Moreover, the minimally invasive nature of liquid biopsies enables a tight and longitudinal tumor monitoring with pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent technological developments have led to the application of a new generation of sequencing techniques, as exemplified through Nanopore sequencing [ 82 , 182 ]. Recently, Afflerbach et al reported a successful genome-wide methylome and copy number analysis of cfDNA in the CSF of glioma patients [ 182 ].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent technological developments have led to the application of a new generation of sequencing techniques, as exemplified through Nanopore sequencing [ 82 , 182 ]. Recently, Afflerbach et al reported a successful genome-wide methylome and copy number analysis of cfDNA in the CSF of glioma patients [ 182 ].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Recent technological developments have led to the application of a new generation of sequencing techniques, as exemplified through Nanopore sequencing [ 82 , 182 ]. Recently, Afflerbach et al reported a successful genome-wide methylome and copy number analysis of cfDNA in the CSF of glioma patients [ 182 ]. This new technology, which enables methylome analysis using extremely small amounts of DNA compared to the conventionally required DNA input, is noteworthy and may open new perspectives for liquid biopsy if it can achieve the inherently relatively high failure rate and improved sensitivity of Nanopore sequencing.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%